Draft Annual Plan 1988-89 Vol. III Uttar Pradesh - Planning Commission (Planning Commission, 1987)
The Planning Commission vide their D.O. letter no. FC (P) 2/87 States/UTs, dated August 21, 1987 have made changes in major and sub-major heads of development on account of which certain programmes/schemes have been shifted from one head to another head resulting in changes in their outlays given in earlier documents.
Government of Uttar Pradesh, Planning Department